The Development of Green Polylactic Acid (PLA)Composites for Wastewater Treatment – A Review - Andriy Anta KACARIBU; Yuliani AISYAH; Febriani FEBRIANI; Darwin DARWIN (Engineering Transactions, 2025)
Polylactic acid (PLA) is a biodegradable polyester derived from renewable resources, recognized for its environmental sustainability and versatile properties. Its applications spam the biomedical, textile, and packaging industries and, more recently, wastewater treatment. This review explores recent advancements in the use of PLA and its composites for wastewater treatment, emphasizing their effectiveness, modification techniques to enhance performance, and future research directions. A thorough literature review was conducted, covering the past decade studies, and, including research articles, reviews, and case studies on PLA’s application in wastewater treatment and comparative performance against other adsorbents. Although PLA’s natural adsorption capacity is limited, it has demonstrated significant potential for removing contaminants such as heavy metals, organic dyes, and other organic pollutants. Various modifications, including surface chemical changes, physical blending with nanomaterials, and more, have notably improved its adsorption performance. Modified PLA composites thus present a viable and sustainable solution for wastewater treatment. Continued research is essential to further optimize these modifications, explore novel composite materials, develop scalable technologies, and assess long-term environmental impacts. This review offers a critical synthesis of current knowledge on PLA-based materials in wastewater treatment, aiming to inform and guide future research in sustainable water purification technologies.